Dental visiting by insurance and oral health impact. (31st July 2013) - Brennan, DS; Anikeeva, O; Teusner, DN
Abstract: Background: The aim of this study was to explore whether oral health has an influence on the association between dental insurance and dental visiting. Methods: A random sample of adults aged 30–61 years living in Australia was drawn from the Australian Electoral Roll. Data were collected by mailed survey in 2009–2010, including age, gender, household income, dental insurance status, dental visiting and oral health impact. Results: Responses were collected from n = 1096 persons (response rate = 39.1%). Dental insurance was positively associated with visiting a dentist in the last 12 months (prevalence ratio (PR) = 1.48; 95% CI: 1.31–1.67), while oral health impact was not associated with recent visiting PR = 1.01; 95% CI: 0.89–1.14). Visiting for the purpose of pain relief was less prevalent among insured participants (PR = 0.60; 95% CI: 0.44–0.81), but more prevalent among those with poor oral health (PR = 2.85; 95% CI: 2.15–3.76). It was found that oral health impact did not alter the relationship between dental insurance and visiting. Conclusions: Oral health impacts were not associated with recent dental visits, but were associated with visits for pain relief. Dental insurance was associated with a greater likelihood of recent visits and lower levels of relief of pain visits.